Cadmium removal by a low-cost magadiite-based material: Characterization and sorption applications. Issue 4 (August 2018) - Attar, Keltoum; Bouazza, Djamila; Miloudi, Hafida; Tayeb, Abdelkader; Boos, Anne; Sastre, Ana M.; Demey, Hary
Graphical abstract: Highlights: Na-magadiite-based materials have been studied for Cd(II) removal from waters. The sorbents were characterized with different techniques (XRD, FTIR, TGA, SEM-EDX). The introduction of Cyanex-272 into the interlayers of Na-Magadiite was studied. The introduction of Cyanex-272 improves the selectivity towards cadmium ions. Abstract: The sorption of cadmium from nitrate medium at room temperature was carried out using solid phase magadiite and magadiite impregnated with Cyanex 272 [bis(2, 4, 4-trimethylpentyl)phosphinic acid]. The sorbent materials have been characterized by X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR), scanning electron microscopy-energy dispersive X-ray analyses (SEM-EDX) and thermogravimetric analysis (TGA/DTG). The UV–vis spectrophotometry technique was used to determine the amount of Cyanex-272 inserted into the solid support. Various parameters such as pH of the aqueous solution, initial Cd(II) concentration and equilibrium time were studied. The sorption data fitted the Sips sorption equation, and the sorption kinetics follows the model of the pseudo-second order. The maximum sorption capacity of Cd(II) was found to be 64.06 mg g −1 and 49.45 mg g −1 (i.e., 0.57 and 0.44 mmol g −1 ) from magadiite and magadiite-Cyanex 272, respectively. The elution of the materials was performed with 0.1 M HNO3 solution, and 80% of the initial sorbed cadmium was recovered.